Konjunkturanalyse for Bornholm, 1987-1996. Kapitel 2: priser og realindkomst - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 1999)
– Real income on Bornholm is described by comparing the region with the capital area and the country. Region specific prices are constructed for housing expenditure and for services. Weights for these parts of household budgets and the residual are found from panel surveys of household consumption. Relative prices of the consumption bundle for each year in the period 1987 to 1996 are found for both those who own there dwelling and those who rent it. Median incomes for entrepreneurs, employees and workers are constructed. Combining data on incomes and on relative prices gives estimates of real incomes. The result is that households of employed persons are relatively rich on Bornholm during the period.
hdl:10398/7609
Keywords: R51; 330; Real income; Bornholm; Prices; Housing expenditure; Services; Household budgets; Denmark